The Effect of Price and Product Quality are able To Create Customer Value Which Ultimately Drives Detergent Purchasing Decisions in Bekasi City - Naomi Frare; Ismail Razak; Iwan Kurniawan Subagja (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
To determine the extent to which price and product quality are able to create customer value which ultimately drives detergent purchasing decisions in Bekasi City. This research is explanatory research through hypothesis testing to examine the effect of price and product quality on purchasing decisions with customer value as a mediating variable. The population of this study is all consumers who use Rinso detergent products in Bekasi City. Because the number of Rinso detergent users in Bekasi City, the population in this study is 2,543,676 (BPS, 2020). The selected respondents are customers domiciled in Bekasi City who have purchased and used detergent at least twice in the last three months, and are at least 18 years old. The sample used in this study uses the Slovin Formula with an alpha of 10%, based on the results of the formula, the number of samples in this study is 100 respondents. The results are regarding the effect of price and product quality on purchasing decisions with customer value as an intermediary variable, that the indicators of price affordability, price suitability with product quality, price comparison with competing products, and price suitability with benefits obtained.